A transcriptomic survey of the impact of environmental stress on response to dengue virus in the mosquito, Aedes aegypti. - David S Kang; Martin S Barron; Diane D Lovin; Joanne M Cunningham; Matthew W Eng; Dave D Chadee; Jun Li; David W Severson (Public Library of Science (PLoS), 2018)
Populations of Aedes aegypti naturally exhibit variable susceptibility to dengue viruses. This natural variation can be impacted by nutritional stress resulting from larval-stage crowding, indicating the influence of environment components on the adult mosquito immune response. In particular, larval crowding was previously shown to reduce the susceptibility of adult females of a Trinidad field isolate of A. aegypti to the dengue serotype 2 (JAM1409) virus. Here, we present the first whole transcriptome study to address the impact of environmental stress on A. aegypti response to dengue virus. We examined expression profiles of adult females resulting from crowded and optimum reared larvae from the same Trinidad isolate at two critical early time points-3 and 18 hours post dengue virus infected blood meal. We exposed specimens to either a dengue or naïve blood meal, and then characterized the response in ten gene co-expression modules based on their transcriptional associations with environmental stress and time. We further analyzed the top 30 hub or master regulatory genes in each of the modules, and validated our results via qRT-PCR. These hub genes reveal which functions are critical to the mechanisms that confer dengue virus refractoriness or susceptibility to stress conditioned A. aegypti, as well as the time points at which they are most important.